Developing Pancasila Character in Early Childhood: Strategies for Working Families - Toto Purbiyanto; Dasim Budimansyah; Encep Syarief Nurdin; Cecep Darmawan; Salman Rashid (Journal of Nonformal Education)
Background: The development of Pancasila character in early childhood is very important, especially in the context of working families who often face challenges in providing optimal character education. The character of Pancasila includes values such as justice, tolerance, and mutual cooperation, which need to be instilled from an early age to form a generation with integrity.